Forage adoption and gaps in Kenya: A review - Mwendia, Solomon W. (Bioversity International and the International Center for Tropical Agriculture, 2020)
Generally, livestock production has remained low in sub-Saharan Africa. One of the key areas with potential to contribute in reversing the situation is use of feeds and feeding. While there are various forages that scientifically have potential to increase productivity, in practice their use has remained low. This short review assesses the current forage adoption in Kenya and the potential to close the gap by use of improved forages. In effect, translates to forage seeds and/or planting materials easily accessible by livestock producers. Equally, there is need of capacity building and awareness creation for the livestock producers to stimulate, harness and bolster forage cultivation for increased livestock productivity.